Kualiti sepintas lalu - Quality at a glance - F. Seling, Tenning; Wee, Cindy; Akir, Oriah; Wan Hassan, Sharifah Zakiah; Ramakrishnan, Prabha; Pereira, Helen; Ghazali, Azlina (Universiti Teknologi MARA, Sarawak, 2004)
Quality at a Glance is a collection of short articles on quality from a myriad of sources compiled by Prof. Adnan Alias. IK will publish a series of these articles starting in this issue. IK thanks Prof Madya Hjh Lelawati for making this book available to us. The following is the first article we have chosen. It was written by Haji Mokhyi Haji Mohd Omar SMS, PPT (Imam Besar, Masjid Sultan Salahuddin Abdul Aziz Shah, Shah Alam, Selangor, Malaysia).